Central Sensitization Phenotypes in Post Acute Sequelae of SARS-CoV-2 Infection (PASC): Defining the Post COVID Syndrome. (July 2021) - Bierle, Dennis M.; Aakre, Christopher A; Grach, Stephanie L.; Salonen, Bradley R; Croghan, Ivana T.; Hurt, Ryan T; Ganesh, Ravindra
Objective: To develop and implement criteria for description of post COVID syndrome based on analysis of patients presenting for evaluation at Mayo Clinic Rochester between November 2019 and August 2020. Methods: A total of 465 patients with a history of testing positive for COVID-19 were identified and their medical records reviewed. After a thorough review, utilizing the DELPHI methods by an expert panel, 42 (9%) cases were identified with persistent central sensitization (CS) symptoms persisting after the resolution of acute COVID-19, herein referred to as Post COVID syndrome (PoCoS). In this report we describe the baseline characteristics of these PoCoS patients. Results: Among these 42 PoCoS patients, the mean age was 46.2 years (median age was 46.5 years). Pain (90%), fatigue (74%), dyspnea (43%), and orthostatic intolerance (38%) were the most common symptoms. The characteristics of an initial 14 patients were utilized for the development of clinical criteria via a modified Delphi Method by a panel of experts in central sensitization disorders. These criteria were subsequently applied in the identification of 28 additional cases of suspected PoCoS. A 2-reviewer system was used to analyze agreement with using the criteria, with all 28 cases determined to be either probable or possible cases by the reviewers. Inter-reviewer agreement using these proposed defining criteria was high with a Cohen's alpha of .88. Conclusions: Here we present what we believe to be the first definitional criteria for Post COVID syndrome. These may be useful in clinical phenotyping of these patients for targeted treatment and future research.